2017
DOI: 10.1104/pp.17.01290
|View full text |Cite
|
Sign up to set email alerts
|

A Tonoplast Sugar Transporter Underlies a Sugar Accumulation QTL in Watermelon

Abstract: How sugar transporters regulate sugar accumulation in fruits is poorly understood and particularly so for species storing high-concentration Suc. Accumulation of soluble sugars in watermelon () fruit, a major quality trait, had been selected during domestication. Still, the molecular mechanisms controlling this quantitative trait are unknown. We resequenced 96 recombinant inbred lines, derived from crossing sweet and unsweet accessions, to narrow down the size of a previously described sugar content quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 49 publications
(70 reference statements)
7
117
0
Order By: Relevance
“…In sugarcane and sweet sorghum, the stems are the principal sink tissues that store very high concentrations of sugars within the parenchyma cells [42][43][44] . Tonoplast sugar transporters (TSTs) have been characterized as sucrose transporters highly associated with vacuolar sucrose accumulation from sugar beet taproot 45 , sugarcane 46 and sweet sorghum stems 47 and watermelon fruit 48 . Whereas there are 3 TST genes in the sorghum genome 47 , the family has expanded in the S. spontaneum genome, which has 4 genes consisting of 13 homologs.…”
Section: Allelic Expression Dominancementioning
confidence: 99%
“…In sugarcane and sweet sorghum, the stems are the principal sink tissues that store very high concentrations of sugars within the parenchyma cells [42][43][44] . Tonoplast sugar transporters (TSTs) have been characterized as sucrose transporters highly associated with vacuolar sucrose accumulation from sugar beet taproot 45 , sugarcane 46 and sweet sorghum stems 47 and watermelon fruit 48 . Whereas there are 3 TST genes in the sorghum genome 47 , the family has expanded in the S. spontaneum genome, which has 4 genes consisting of 13 homologs.…”
Section: Allelic Expression Dominancementioning
confidence: 99%
“…A second GWAS signal associated with flesh color was found on chromosome 2 within the sweetness QTL QBRX2-1 (Fig. 2c); this QTL harbors the candidate gene ClTST2, which, when overexpressed, causes elevated sugar levels in fruit and also leads to flesh color development 35 . A previous study showed that an elevated sugar level activates the watermelon fruit chromoplast-localized phosphate transporter ClPHT4;2 (Cla97C10G205070), the function of which is necessary for carotenoid accumulation in fruit flesh 36 .…”
Section: Chr05mentioning
confidence: 99%
“…Beyond such transporter identification and correlative studies, this report points to the potential contribution of natural allelic variation for sugar transporter genes to the improvement of fruit sugar accumulation, and the results of the present report extend the potential for the contribution of wild species to fruit sugar composition to include this mechanism of accumulation. Recently, a GWAS study of watermelon fruit pointed to a TST sugar transporter, indicating genetic variability (Ren et al, 2018). In light of the presence of orthologs of the SWEET protein present in fruit of other plant species, as well as the expression of other paralogs of SWEET in tomato and other fruit, it is likely that modulation of these orthologs and paralogs may affect the sugar content of tomato and other fruits, as well.…”
Section: Solyc04g064640 Imentioning
confidence: 99%